Wiper Protection / Mohammad Nazir Marzuki - Marzuki, Mohammad Nazir (2007)
This project generally introduces to make the wiper of the car can stand last longer. Generally, this project consists of temperature sensor, microcontroller (PIC) and stepped motor. Temperature sensor senses the temperature and sends data to peripheral interface controller the process data given. Then the peripheral interface controller sends data to stepped motor to make an appropriate action. This project will help the car user to make their wiper can stand last longer.